Urgensi Pendidikan Inklusif: Membangun Lingkungan Pembelajaran Yang Mendukung Kesetaraan Dan Kearifan Budaya - Norsandi, Dedy; Wisman, Yossita; Alamsyah, Iwan Noor; Bernisa, Bernisa (Jurnal Ilmiah Kanderang Tingang, 2025)
In this era of educational progress, challenges and opportunities continue to emerge, and one of the educational paradigms that is increasingly being paid attention to is inclusive education. This research aims to dive deeper into the concept of inclusive education, exploring the importance of building learning that supports equality and implementing cultural wisdom values in it. This research method uses descriptive qualitative with literature study. Inclusive learning that combines equity and cultural wisdom involves a variety of strategies, including the use of learning methods, culturally responsive curricula, parent participation, and diverse assessments. By bringing all aspects together, teachers can create a learning environment that supports equality, respects cultural diversity, and allows each student to reach his or her potential optimally.